Social Science Research on Development: Some Problems in the Use and Transfer of an Intellectual Technology - Streeten, Paul P.; Gordon, Anne; Rubery, Jill; Hirsch, Seev; Stretton, Hugh; Virmani, B. R.; Winston, Gordon C. (Journal of Economic Literature, 2016)
I have benefited from comments and criticisms of an earlier draft by Irma Adelman, Peter Balacs, Ronald Dore, Edgar Edwards, Unni Eradi, Michael Faber, Anne Gordon, Keith Griffin, Jill Rubery, Seev Hirsch, Ernest Stern, Frances Stewart, Hugh Stretton, B. R. Virmani, Gordon Winston and Howard Wriggins. To these, and to a research seminar at Queen Elizabeth House, I am very grateful. I am also grateful to the Economic Development Institute of the World Bank and its Director, Mr. Andrew Kamarck, for having provided the facilities and stimulating atmosphere for the early stages of a considerably larger paper, commissioned by Mr. Ernest Stern, of which this paper forms a part. I am grateful to Mr. Stern and the World Bank for permitting me to use the material here.